THE FORM OF PROLETARIAN RESISTANCE IN THE NOVEL HAMAMAH SALAAM BY NAJIB KAILANI (A MARXIST LITERARY SOCIOLOGY APPROACH) - Asep Nurkholis; Dedi Supriadi; Yadi Mardiansyah (Esteem Journal of English Education Study Programme, 2025)
Literary works often serve as mirrors reflecting the socio-political dynamics within a society, making them fertile ground for analysis through the lens of the sociology of literature. Marxist theory, in particular, offers a critical framework for examining the social structures and power relations embedded in literary texts. One prominent example is Najib Kailani, whose writings especially the novel Hamamahus Salaam are deeply influenced by his socio-cultural background and educational exposure, manifesting in narratives of resistance and social critique. This study adopts a descriptive-analytic approach, gathering data in the form of linguistic expressions, including words, phrases, sentences, and dialogues, to interrogate the presence of class conflict and proletarian resistance within the novel. The analysis reveals key indicators of class struggle, primarily stemming from: (1) systemic exploitation and oppression, (2) the emergence of social consciousness among the marginalized, and (3) the complicity of ideological state apparatuses or superstructures. The manifestations of resistance identified in the text include: (1) the development of proletarian class awareness, (2) collective defiance against oppressive forces, (3) acts of repressive sabotage, (4) the strategic formation of resistance groups, and (5) direct confrontational actions, including threats of violence. Through these elements, the novel articulates a potent critique of class-based injustices and advocates for collective agency among the oppressed.